EVALUATION OF THE INCLUSIVE VILLAGE PROGRAM IN ACHIEVING SUSTAINABLE DEVELOPMENT GOALS (CASE STUDY: KENDAL VILLAGE, ASTANAJAPURA SUB-DISTRICT, CIREBON REGENCY) - Yolanda, Farrah
The Sustainable Development Goals (SDGs) aim to promote the fulfillment of rights for marginalized communities. Eleven out of the seventeen SDGs agendas are focused on addressing social issues related to inclusivity. The inclusive village program serves as one of the implementation strategies to tackle the challenges of inclusivity, particularly in ensuring the fulfillment of rights and participation of individuals with disabilities. This research aims to evaluate the village inclusion program in achieving sustainable development goals by identifying criteria and indicators for program assessment, subsequently assessing the program using the identified criteria and indicators, and finally formulating strategies for enhancing the village inclusion program in achieving sustainable development goals in Kendal Village. The study adopts a mixed methods approach, utilizing questionnaires, interviews, observations, and literature reviews as sources of information. The criteria and indicators used to measure the inclusive village program are developed based on various literature studies related to SDGs, inclusive villages, and rural development. The research findings indicate that the majority of rights for individuals with disabilities and People Affected by Leprosy (PAL) have been fulfilled. However, this does not apply to the provision of educational facilities and infrastructure, improvement of economic opportunities through decent jobs and career development, as well as their participation in various activities. In this context, effective strategies are needed to enhance the implementation of the inclusive village program. Despite the completion of the program, it is crucial to conduct monitoring and supervision to ensure the continued progress of inclusive rural development. Fundamentally, an inclusive village can be defined as a community that actively embraces and positively values differences while encouraging the participation of its members in the development and advancement of the village.